Reawakening of Ancestral Dental Potential as a Mechanism to Explain Dental Pathologies - Hovorakova, Maria; Zahradnicek, Oldrich; Bartos, Martin; Hurnik, Pavel; Stransky, Jiri; Stembirek, Jan; Tucker, Abigail S (Integrative and comparative biology, 2020)
During evolution, there has been a trend to reduce both the number of teeth and the location where they are found within the oral cavity. In mammals, the formation of teeth is restricted to a horseshoe band of odontogenic tissue, creating a single dental arch on the top and bottom of the jaw. Additional teeth and structures containing dental tissue, such as odontogenic tumors or cysts, can appear as pathologies. These tooth-like structures can be associated with the normal dentition, appearing within the dental arch, or in nondental areas. The etiology of these pathologies is not well elucidated. Reawakening of the potential to form teeth in different parts of the oral cavity could explain the origin of dental pathologies outside the dental arch, thus such pathologies are a consequence of our evolutionary history. In this review, we look at the changing pattern of tooth formation within the oral cavity during vertebrate evolution, the potential to form additional tooth-like structures in mammals, and discuss how this knowledge shapes our understanding of dental pathologies in humans.
Keywords: ústa; savci; odontogeneze; obratlovci; Biological Evolution; Tooth; Animals; Humans; zuby; lidé; Vertebrates; Odontogenesis; zvířata; Mammals; biologická evoluce; Mouth